Carbon dots-based nanocarrier system with intrinsic tumor targeting ability for cancer treatment. (19th October 2020) - Yang, Xiaojing; Wang, Yingying; Du, Xiangfu; Xu, Jingjing; Zhao, Mei-Xia
Abstract: Doxorubicin (DOX) is a traditional broad-spectrum antitumor drug, which has a wide range of clinical applications, but has no tumor non-specificity. Nanoparticles have been explored as drug delivery agents to enhance the therapeutic efficacy and reduce toxic and side effects. Carbon dots (CDs), a carbon-based nanomaterial, has many unique advantages such as easy synthesis, good biocompatibility, and low toxicity. In this study, folic acid was used as raw material to prepare new CDs, and DOX was loaded on the surface of CDs through electrostatic interaction. The prepared nano-drugs CDs/DOX could effectively release DOX under mild acidic pH stimulation. Cell imaging showed that CDs/DOX could transport doxorubicin (DOX) to cancer cells and make them accumulated in nucleus freely. Flow cytometry tests and cellular toxicity assay together confirmed that CDs/DOX could target tumor cells with high expression of folate receptor and increase anti-tumor activity. The therapeutic effect on 4T1 tumor-bearing mice model indicated that CDs/DOX could alleviate DOX-induced toxicity, effectively inhibit tumor growth, and prolong the survival time. Hence, such a targeting nanocarrier is likely to be a candidate for cancer treatment.